Blockchain, Crypto Assets, and Financial Innovation - Gang Kou; Yongqiang Li; Zongyi Zhang; J. Leon Zhao; Zhi Zhuo (Springer Nature Singapore, 2025)
This open access book provides a decade-spanning, meticulously curated collection of research that showcases groundbreaking advances in blockchain, cryptocurrency, digital finance, and market volatility. Through empirical studies, predictive models, and comprehensive reviews, this book reveals the evolution of financial innovation over the past decade, highlighting blockchain as a transformative direction alongside other pivotal advancements, with both theoretical insights and actionable applications. It's a paper selection from Financial Innovation journal, with the necessary revision for inclusion, and aims to trace and refine the research on financial technology during the past 10 years. With its pioneering focus on emerging topics—such as innovative blockchain applications in finance, the rise of tokens and NFTs as digital assets, and cryptocurrency market dynamics—this book delves into cutting-edge financial phenomena rarely covered in traditional finance literature. Spanning complexities from market dynamics, volatility, and spillover effects to the evolving regulatory landscape for crypto adoption, it provides readers with a comprehensive understanding of blockchain's role in modern finance. Intended for researchers, academics, policy makers, and finance professionals, this book balances rigorous academic research with real-world applicability, providing insights that appeal to both scholarly and practical perspectives. Key benefits include a unique mix of strategic advances in financial innovation and actionable research insights for navigating its evolving landscape.